COMPARATIVE STUDY OF ENGLISH COPULA AND ITS EQUIVALENCE IN INDONESIAN - Aziz, Muhyiddin (Humaniora Scientia, 2014)
The research discusses about the kinds and structures of copula, and the similarities and differences of English copula and its equivalence in Indonesian.Â There are three problems which must be answered. First, the problem discusses the kinds of copula in English. Second, the problem discusses the structure of copula in English. Third, the problem discusses the similarities and differences of English copula and its equivalence in Indonesian. This research uses descriptive method, equivalence method and distributional method to analyze the data taken from novel Agatha Christieâ€™s The Mysterious Mr. Quin and Mr. Quin yang Misterius, Indonesian translation version by Julanda Tanti through total sampling technique. There are three findings of this research. They are (1) the kinds of English copulas, namely copula be and copulative verd dividing into two kinds, namely verb and linking verb; (2) the structures of English copulas dividing into three patterns, that is, (Noun+Copula+Adjective), (Noun+Copula+Adverb), and (Noun+Copula+Noun); and (3) the similarities and differences of copulas in English and its equivalence in Indonesian dividing into two kinds, that is, the similarities of English and Indonesian copulas, and the differences of English and Indonesian copulas are based on the obligation of its occurrence. Key words: Copula, Verb, linking verb.